Pengaruh Intensitas Modal, Debt Convenant, Dan Risiko Litigasi Terhadap Konservatisme Akuntansi - Naimah; Elvina Setiawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to examine the influence of capital intensity, debt convenants, and litigation risk on accounting conservatism in manufacturing companies in the consumer goods industry sector listed on the IDX in 2017-2022). So this research variable consists of 3 (three) independent variables, namely capital intensity (X1), debt convenant (X2), litigation risk (X3) and the dependent variable, namely accounting conservatism (Y). The population of this research is 78 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. Samples were taken using a sampling technique, namely purposive sampling. The sampling method uses a purposive sampling method. Based on predetermined criteria, a sample size of 8 companies was obtained during 6 years of observation. Hypothesis testing uses multiple linear regression analysis. The analytical tool that will be used in this research is a statistical analysis technique based on computer software using the Statistical Product and Service Solutions (SPSS) program version 27. The results of this research are that capital intensity has no effect on accounting conservatism, debt convenants have a negative effect on accounting conservatism. , and litigation risk have a negative effect on accounting conservatism. The results of this research also show that accounting conservatism is influenced by Capital Intensity, Debt Covenant and Litigation Risk by 21%, while the remaining 79% is influenced by other factors not examined in this research